1994
DOI: 10.1103/physrevd.50.3801
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of black hole apparent horizons

Abstract: Dynamic black hole spacetimes are studied by examining the evolution of apparent horizons surrounding the holes. We performed numerical evolutions of three different initial data sets: nonrotating black holes distorted by time symmetric (Brill) gravitational waves, distorted rotating black holes, and the time symmetric two black hole Misner data. Although the initial data sets represent different physical problems, the results for these systems are strikingly similar. At early times in the evolution, the appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
100
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(101 citation statements)
references
References 26 publications
0
100
1
Order By: Relevance
“…In this first paper in this series we present details of a numerical code designed to evolve rotating black hole initial data sets, such as Kerr, Bowen and York [3], and a new class of data sets we have developed [8]. With such a code we can now study the dynamics of highly distorted, rotating black holes, paralleling recent work of the NCSA group on non-rotating holes [9,10]. The first studies of the physics of these evolving systems are presented in a companion paper [11], referred to henceforth as Paper II, and a complete study of the initial data sets will be discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this first paper in this series we present details of a numerical code designed to evolve rotating black hole initial data sets, such as Kerr, Bowen and York [3], and a new class of data sets we have developed [8]. With such a code we can now study the dynamics of highly distorted, rotating black holes, paralleling recent work of the NCSA group on non-rotating holes [9,10]. The first studies of the physics of these evolving systems are presented in a companion paper [11], referred to henceforth as Paper II, and a complete study of the initial data sets will be discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…As in Ref. [9], the conformal factor Ψ is determined on the initial slice and, since we do not use it as a dynamical variable, it remains fixed in time afterwards. The introduction of Ψ into the extrinsic curvature variables simplifies the evolution equations somewhat.…”
Section: B Definition Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the location of such horizons is obtained only in coordinate space, one typically has little information about the real geometry of those surfaces. One can, for example, obtain very similar shapes in coordinate space for horizons that are in fact very different (see for example the family of distorted black holes studied in [1]; their coordinate locations are very similar, but their geometries are quite different). The most natural way to visualize the geometry of a black-hole horizon, or of any other surface computed in some abstract curved space is to find a surface in ordinary flat space that has the same intrinsic geometry as the original surface.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that for rapidly rotating black holes, with a/m > √ 3/2, the Gaussian curvature becomes negative near the poles, and the surface is not embeddable in Euclidean space, as it is 'too flat'! Extending on this paper, using a direct constructive embedding method described below, a number of studies were made of distorted, rotating and colliding black-hole horizons in axisymmetry [1,[6][7][8][9][10] where it was shown that embeddings are very useful tools to aid in the understanding of the dynamics of black holes. For example, distorted rotating black-hole horizons were found to oscillate, about their oblate equilibrium shape, at their quasi-normal frequency.…”
Section: Introductionmentioning
confidence: 99%